Urgensi Penguatan Peran Jaksa Penuntut Umum dalam Sistem Peradilan Pidana Indonesia - Septiani, Veni; Dika Ratu Marfuatun (KRAKATAU (Indonesian of Multidisciplinary Journals), 2023)
This study aims to determine the urgency of strengthening the role of public prosecutors in the Indonesian criminal justice system, this type of research uses normative methods with statutory and conceptual approaches. Article 1 paragraph (1) of Law Number 16 of 2004 concerning prosecutors, prosecutors are functional officials authorized to act as public prosecutors by law, and executors of court decisions that have obtained permanent legal force and other powers. Article 1 paragraph 6 (b) of Law Number 8 of 1981 concerning criminal procedure, hereinafter referred to as the Criminal Procedure Code (KUHAP), a public prosecutor is a prosecutor authorized by law to conduct prosecutions and execute judges' decisions. The Public Prosecutor's Office as a subsystem of criminal justice is regulated through Law Number 16 of 2004 concerning the Public Prosecutor's Office of the Republic of Indonesia.